The impact of artificial intelligence technologies on improving foreign language teaching methods - Шабуніна, Вікторія Віталіївна; Лабенко, Оксана Викторівна; Горбаченко, Анна Леонідівна (Всеукраїнська асамблея докторів наук з державного управління, 2024)
The article examines the impact of artificial intelligence (AI) technologies on improving foreign language teaching methods in higher education institutions. The relevance of the study is stipulated by the need toincrease the efficiency of learning amidst the rapid development of distance and online education formats. The objective of this article is to examine the impact of AI on enhancing the effectiveness of foreign language instruction in higher education institutions, as well as to propose recommendations for optimizing these processes through the application of artificial intelligence technologies. It is emphasized that there is a great potential for personalizing the learning experience, improving students’ communication abilities, and alleviating educators’ workloads. The research methods include scientific literature review, comparative analysis, and empirical investigation of AI-driven interactive platforms in prominent Ukrainian universities. A survey was conducted to gather data on the current level of AI integration into the educational process and its influence on learning outcomes.The results of the study show that AI-based interactive platforms have a positive impact on students’ engagement in the learning process, increase their motivation, and ensure constant access to educational materials. For instance, the use of chatbots for language practice improves communication skills, while speech recognition systems help students perfect their pronunciation. However, along with positive results, several challenges were identified, including technical limitations, unstable internet connections due to the war, insufficient teacher preparation for working with new technologies, and difficulties in accounting for students’ emotional states.The conclusions outline recommendations for educational institutions on the implementation of AI technologies in the learning process. In particular, it is recommended to modernize the technical infrastructure of universities, organize training for teachers on AI usage, and elaborate both adaptive learning and student centered programs. Prospects for further research are related to the development of new pedagogical models that integrate AI with consideration of sociocultural factors as well asensure improved learning efficiency in the times of crisis.

У статті досліджено вплив технологій штучного інтелекту (далі – ШІ) на вдосконалення методик викладання іноземних мов у закладах вищої освіти (далі – ЗВО). Актуальність дослідження зумовлена необхідністю підвищення ефективності навчання в умовах стрімкого розвитку дистанційних та онлайн-форматів освіти. Метою статті є аналіз впливу ШІ на підвищення ефективності викладання іноземних мов у ЗВО, а також розробка рекомендацій щодо оптимізації цих процесів із використанням технологій штучного інтелекту. Особлива увага приділяється можливостям персоналізації освітнього процесу, покращенню комунікативних навичок здобувачів вищої освіти та полегшенню навантаження на викладачів.У межах дослідження було використано методи аналізу наукових джерел, порівняльний аналіз та емпіричні дослідження впровадження інтерактивних платформ на основі ШІ в провідних українських ЗВО. Проведено опитування, що дозволило зібрати дані про реальний рівень інтеграції ШІ в освітній процес та оцінити його вплив на результати навчання.У дослідженні продемонстровано, що інтерактивні платформи на основі ШІ мають позитивний вплив на залученість здобувачів до освітнього процесу, підвищують рівень мотивації та забезпечують постійний доступ до навчальних матеріалів. Наприклад, використання чат-ботів для мовної практики сприяє покращенню комунікативних навичок, а системи розпізнавання мовлення допомагають здобувачам покращити вимову. Проте, разом із позитивними результатами, виявлено низку проблем, серед яких технічні обмеження, нестабільність інтернет-зв’язку через війну, недостатня підготовка викладачів до роботи з новими технологіями та труднощі врахування емоційного стану здобувачів вищої освіти.У висновках сформульовано рекомендації для ЗВО щодо впровад-ження технологій ШІ в освітній процес. Зокрема, рекомендується модернізувати технічну базу ЗВО, організовувати тренінги для викладачів із використання ШІ та розробляти адаптивні освітні програми, що враховують індивідуальні потреби здобувачів. Перспективи подальших досліджень пов’язані з розробкою нових педагогічних моделей, що інтегрують ШІ з урахуванням соціокультурних факторів та забезпечують підвищення ефективності навчання в умовах кризи.
Вплив технологій штучного інтелекту на покращення методик викладання іноземних мов
Keywords: штучний інтелект; викладання іноземних мов; персоналізація навчання; інтерактивні платформи; дистанційнаосвіта; технології; заклади вищої освіти; artificial intelligence; foreign language teaching; personalized learning; interactive platforms; distance education; technologies; higher education institutions